New data on the parasitism of citrus leafminer (Phyllocnistis citrella Stainton, Lep. Gracillariidae) in Sicily (Bollettino di zoologia agraria e bachicoltura, 2024)
From March to October 1998 the parasitism trend on citrus leafminer (CLM) was studied in two unsprayed orange groves of Agrigento province. In order to evaluate the parasitoid complex, samples were also collected, in the same period, in three other citrus groves. The leafminers of the spontaneous vegetation inside and near the orange groves were also investigated, with the aim of recording the Eulophid species known as parasitoids of CLM. Because of the significant correlation resulted between the parasitism rate calculated as mature larvae and pupae of parasitoids compared with CLM pupae and the parasitism rate on L3, L4 and pupae, the first index was preferred, representing an easier way to assess the parasitism, especially when a large number of samples have been collected. During the spring flush CLM infestation was almost absent; in summer an increasing parasitism has been recorded in both orchards, reaching the maximum in September, 87.5% at Ribera and 24% at Menfi. A maximum mean value in this month was also recorded in the previous years. In the orange groves the total parasitism was 47.2% at Ribera and 9% at Menfi. In 1998 the parasitism due to of Eulophid parasitoids showed an increase (from 9.8% in 1995-97 to 18.1%), mainly due to the addition of Semielacher petiolatus (Girault) activity. This exotic species, although found only from August 1998, reached at Ribera interesting values of parasitism (83.3%). In 1998, as in the previous years, Cirrospilus pictus (Nees) was the most abundant parasitoid species, but in two citrus groves S. petiolatus was the main parasitoid. Nevertheless the parasitoid complex in Sicily was unable to influence noticeably the CLM infestation. Though the differences observed on the spontaneous vegetation inside and near the two orange groves, at the moment we have no evidences to state that the presence of alternative hosts of CLM Eulophid parasitoids on  spontaneous plants could greatly influence the parasitism on P. citrella. Phyllocnistis saligna (Zeller), found infesting Salix alba L., is here recorded as another host of Cirrospilus diallus Walker; Caloptilia stigmatella (F.) on Populus nigra L. was found for the first time as host of Pnigalio agraules Walker.